2008
DOI: 10.1093/cvr/cvn286
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibition increases lipopolysaccharide-induced atherosclerosis in mice

Abstract: The inhibition of COX-2-derived PGE(2) may enhance P. gingivalis LPS-induced atherosclerosis by increasing macrophage production of TNFalpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 33 publications
(51 reference statements)
2
41
0
1
Order By: Relevance
“…Additionally, the dampened HPA response in indomethacin-treated animals likely reduced glucocorticoid inhibition of inflammatory cytokine production resulting in widespread increases in inflammatory cytokine production. These data are of particular interest because nonsteroidal anti-inflammatory drugs are commonly used for the relief of pain and inflammation, yet chronic use is associated with an increased risk of atherosclerosis and thrombosis (6,25,28). It is possible that COX inhibitors create a prothrombotic state by elevating proinflammatory cytokines responses, which upregulate adhesion molecules on endothelial cells promoting leukocyte adhesion and aggregation to vessel walls and increase the production of tissue factor while simultaneously preventing the formation of PGI 2 that typically inhibit proinflammatory cytokine production (44,64) as well as platelet activation (7) and aggregation (4,9,29,33,42).…”
Section: R1653 Time-dependent Mediators Of the Hpa Axis Following E mentioning
confidence: 99%
“…Additionally, the dampened HPA response in indomethacin-treated animals likely reduced glucocorticoid inhibition of inflammatory cytokine production resulting in widespread increases in inflammatory cytokine production. These data are of particular interest because nonsteroidal anti-inflammatory drugs are commonly used for the relief of pain and inflammation, yet chronic use is associated with an increased risk of atherosclerosis and thrombosis (6,25,28). It is possible that COX inhibitors create a prothrombotic state by elevating proinflammatory cytokines responses, which upregulate adhesion molecules on endothelial cells promoting leukocyte adhesion and aggregation to vessel walls and increase the production of tissue factor while simultaneously preventing the formation of PGI 2 that typically inhibit proinflammatory cytokine production (44,64) as well as platelet activation (7) and aggregation (4,9,29,33,42).…”
Section: R1653 Time-dependent Mediators Of the Hpa Axis Following E mentioning
confidence: 99%
“…Several studies have reported that repeated injections of endotoxin in animals significantly accelerates atherosclerosis, suggesting that LPS-induced immune mechanisms play an important role in the atherosclerotic process 5,23,24) . The findings of the present study are consistent with those of the above studies, although they are in direct contrast with the results of earlier studies in which no proatherogenic effects of endotoxin administration were observed in piglets or rabbits fed a high-cholesterol diet 25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…One potentially important source of inflammation is endotoxin. Previous studies have indicated a relationship between endotoxin and atherosclerosis 5,6) . In the present study, a simple rabbit model of LPS-induced spontaneous carotid atherosclerotic thrombosis was established using a cholesterol-enriched diet and balloon injury to the target artery.…”
Section: Oct Image Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…Semakin kuat intensitas warna semakin kuat ekspresi COX-2. Hal ini sesuai dengan hasil penelitian 15 bahwa protein COX-2 terekspresi pada sel inflamasi, sel endotel, fibroblas gingiva dan sel epitel pada gingiva yang terinflamasi.…”
Section: Pembahasanunclassified